New materials based on InP-ZnS system for semiconductor gas analyzers - I. A. Kirovskaya; R. V. Ekkert; A. O. Ekkert; E. V. Mironova; I. Yu. Umansky; A. I. Blesman; D. A. Polonyankin; L. V. Kolesnikov; E. N. Kopylova; V. B. Goncharov (Омский научный вестник)
According to the developed methodology, based on the isothermal diffusion of the initial binary compounds (InP, ZnS), their physical and physicochemical properties, solid solutions of different composition ((InP)x (ZnS)1-x) have been obtained. X-ray examinations have been conducted which allows to certify them as substitution solid solution with sphalerite structure and acid-base properties studies (pH isoelectric state — pHISO). The consistent patterns of changes in the composition of the studied (bulk and surface) properties, which are of predominantly smooth nature, have been established. A correlation between theoretical calculated crystal density and acid sites strength (pHISO) has been found which served as the basis for recommending a less labour-consuming way to search for the advanced materials for semiconductor gas analyzers.